Perfect phrases for managing your small business - Bacal, Robert (Mc-GrawHill, 2009)
As a small business owner, you may find yourself overwhelmed with endless chores, decisions, and day-to-day responsibilities. Communicating clearly with everyone from vendors to employees is critical to your success. Perfect Phrases for Managing Your Small Business provides the phrases you’ll need to take charge, perform your tasks, and succeed in these trying times. Inside you’ll find: Hundreds of quick, ready-to-use concepts and phrases for nearly every business situation. Targeted coverage on topics, from starting your business to hiring and motivating employees to dealing with challenging customer situations. How to market and sell your products and services.